High autonomy and low accountability: Case study of five Czech schools - Dominik Dvořák; Petr Urbánek; Karel Starý (Czech Pedagogical Society, 2014)
The paper aims to describe the effects of a unique combination of high autonomy and low outcome accountability of the Czech schools. First, the paper outlines test-based accountability as a key concept of contemporary educational policy. Next, the research design is briefly described and the qualitative data on the effects of school choice and curriculum autonomy / decentralisation are presented. The discussion stresses the problem of time frame in evaluating system wide interventions and also sketches a vision of new emerging school reform discourse. Processes of change in five Czech "combined" primary and lower secondary schools were studied by qualitative longitudinal multiple case study for over 5 years. Surprisingly, the results suggest that many negative effects ascribed to the highstakes tests (e. g. curriculum narrowing, fabrication of image) could be seen in the studied schools despite the different model of governance in the Czech Republic. The contemporary discussion of risks of (high stake) testing should be complemented by a similar analysis of both costs and negative effects of the absence of outcome accountability.